2022
DOI: 10.3390/agriculture12050592
|View full text |Cite
|
Sign up to set email alerts
|

Does Cognition of Resources and the Environment Affect Farmers’ Production Efficiency? Study of Oasis Agriculture in China

Abstract: Improving production efficiency can help overcome the constraints of resource scarcity and fragile environments in oasis agriculture. However, there are few studies about the effect of farmers’ cognition of resources and the environment on their production efficiency. Taking farmers in the Ganzhou District of Zhangye—a typical representative of oasis agriculture in an inland river basin in Northwest China—this study empirically analyzed the effect of farmers’ cognition of resources and the environment on agric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Ecological cognition mainly includes the perception of ecological status [31], the knowledge of ecological policies [28], the awareness of responsibility for ecological protection [51], and the understanding of green production and living actions [52,53]. The bounded rationality hypothesis of behavioral economics suggests that information incompleteness due to limited ecological cognitive capacity constrains the rational limits of farmers' green production behavior [54,55].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Ecological cognition mainly includes the perception of ecological status [31], the knowledge of ecological policies [28], the awareness of responsibility for ecological protection [51], and the understanding of green production and living actions [52,53]. The bounded rationality hypothesis of behavioral economics suggests that information incompleteness due to limited ecological cognitive capacity constrains the rational limits of farmers' green production behavior [54,55].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Ecological cognition can effectively drive farmers to adopt green production [30][31][32]. Zhang et al [33] based on the data from 924 Chinese farmers concluded that ecological concerns contributed the most to farmers' willingness to reduce pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…In order to reach the targets, it is necessary to enhance the endogenous power of carbon reduction in agriculture from the following two perspectives. Firstly, peasants' perceptions of the necessity and benefits of green production profoundly influence their production 2 of 19 behaviour [3]. The effective transmission of environmental and market information will encourage peasants to engage in green produce and achieve carbon reduction in agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the factors influencing farmers' adoption of soil testing and fertilizer application technology has focused on two aspects: first, it is influenced by micro factors, such as farmers' production and management characteristics, individual cognition, and willingness (Guo et al, 2022); second, it is influenced by macro governance factors, such as government regulation and organizational linkages, involving regulatory instruments, such as agricultural environmental control, agricultural technology promotion and dissemination, government subsidies, and services provided by agricultural cooperative organizations through the provision of market demand information and standardized technology guidance (Bonnet et al, 2020). The results of previous research are of great significance and reference value to this paper, but there is still room for further improvement.…”
Section: Introductionmentioning
confidence: 99%